A dynamic inversion approach for oscillation-free control of overhead cranes - Padula, Fabrizio; Visioli, A.; Facchinetti, D.; Saleri, A. (2015)
© 2015 IEEE.In this paper an approach for controlling overhead cranes by avoiding oscillations is proposed and experimentally tested. In particular, a dynamic inversion technique is applied to the overhead crane model to design suitable (position or velocity) set-point and torque feedforward signals. The inversion approach is further simplified in order to make the proposed methodology more industrial-oriented. Experimental results, obtained by using a scaled overhead crane built by using only off-the-shelf components, show the effectiveness of the proposed methodology.